Simultaneous Determination of AFB1 and AFM1 in Milk Samples by Ultra High Performance Liquid Chromatography Coupled to Quadrupole Orbitrap Mass Spectrometry - Rodriguez-Carrasco, Yelko; Izzo, Luana; Gaspari, Anna; Graziani, Giulia; Manes, Jordi; Ritieni, Alberto (Mycotoxins: An Under-evaluated Risk for Human Health, 2022)
Milk is the world’s most consumed beverage, not counting water. Even though investigations on milk aflatoxin (AF) M1 contamination are regularly conducted, there is limited information on the contamination of milk with its parent compound, AFB1. Hence, the aim of this study was to develop a quick, easy, cheap, effective, rugged, and safe (QuEChERS)-based method for the simultaneous analysis of AFB1 and AFM1 in milk, using ultrahigh performance liquid chromatography coupled with high resolution mass spectrometry (UHPLC-Q-Orbitrap HRMS). The recoveries were in a range of 75–96% at 0.005, 0.01, and 0.05 \(μ /L\) spiking levels, with repeatability and reproducibility results expressed as relative standard deviations (RSDs) lower than 7% and 16%, respectively. The limits of detection (LODs) and quantification (LOQs) were 0.001 and 0.002 \(μ /L\) for AFM1 and AFB1, respectively. The LODs and LOQs that were obtained showed the suitability of the developed method for the determination of trace amounts of the selected mycotoxins in milk samples, and were up to ten times lower than those that had been reported in previous works using triple quadrupole mass analyzers. The matrix effect was evaluated and matrix-matched calibrations were used for quantification. The validated method was applied to 40 Italian milk samples. Neither AFB1 nor AFM1 were found above the LOD in any of the analyzed samples.